ANALYSIS OF COMPOSITE ELECTRIC VEHICLE BODY - Lydia Anggraini; Ida Bagus Madra Gana (Journal of Mechanical Engineering and Mechatronics, 2020)
This paper presents a study of a composite car body using finite element method. The body is made of surface model and the study is conducted to simulate the possible deformation of the body under certain load. The objective is to find tha ideal thickness of the composite body as to minimize the vehicle weight. In this research, the strength analysis using finite elements will be explained and the deformation of the body is investigated for finding a possibility to improve this research.